The emergence of multi-drug resistant and virulence gene carrying Escherichia coli strains in the dairy environment: a rising threat to the environment, animal, and public health - Shoaib, Muhammad; He, Zhoulin; Geng, Xiang; Tang, Minjia; Hao, Ruochen; Wang, Shengyi; Shang, Ruofeng; Wang, Xuehong; Zhang, Hongjuan; Pu, Wanxia (Frontiers in Microbiology, 2023)
Escherichia coli is a common inhabitant of the intestinal microbiota and is responsible for udder infection in dairy cattle and gastro-urinary tract infections in humans. We isolated E. coli strains from a dairy farm environment in Xinjiang, China, and investigated their epidemiological characteristics, phenotypic and genotypic resistance to antimicrobials, virulence-associated genes, and phylogenetic relationship. A total of 209 samples were collected from different sources (feces, slurry, water, milk, soil) and cultured on differential and selective agar media (MAC and EMB). The presumptive identification was done by the VITEK2 system and confirmed by 16S rRNA gene amplification by PCR. Antimicrobial susceptibility testing was done by micro-dilution assay, and genomic characterization was done by simple and multiplex polymerase chain reaction (PCR). A total of 338 E. coli strains were identified from 141/209 (67.5%) of the samples. Most of the E. coli strains were resistant to sulfamethoxazole/trimethoprim (62.43%), followed by cefotaxime (44.08%), ampicillin (33.73%), ciprofloxacin (31.36%), tetracycline (28.99%), and a lesser extent to florfenicol (7.99%), gentamicin (4.44%), amikacin (1.77%), and fosfomycin (1.18%). All of the strains were susceptible to meropenem, tigecycline, and colistin sulfate. Among the resistant strains, 44.4% were identified as multi-drug resistant (MDR) showing resistance to at least one antibiotic from ≥3 classes of antibiotics. Eighteen out of 20 antibiotic-resistance genes (ARGs) were detected with sul2 (67.3%), blaTEM (56.3%), gyrA (73.6%), tet(B) (70.4%), aph(3)-I (85.7%), floR (44.4%), and fosA3 (100%, 1/1) being the predominant genes among different classes of antibiotics. Among the virulence-associated genes (VAGs), ompA was the most prevalent (86.69%) followed by ibeB (85.0%), traT (84.91%), ompT (73.96%), fyuA (23.1%), iroN (23.1%), and irp2 gene (21.9%). Most of the E. coli strains were classified under phylogenetic group B1 (75.45%), followed by A (18.34%), C (2.96%), D (1.18%), E (1.18%), and F (0.30%). The present study identified MDR E. coli strains carrying widely distributed ARGs and VAGs from the dairy environment. The findings suggested that the dairy farm environment may serve as a source of mastitis-causing pathogens in animals and horizontal transfer of antibiotic resistance and virulence genes carrying bacterial strains to humans via contaminated milk and meat, surface water and agricultural crops.